Analisis dan Prototype Website Akademik untuk Meningkatkan Sarana Media Informasi Sekolah - Rd. Elin Tahlinia Lutfiah; Muhammad Taufiq; Hani Rubiani (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
Advancements in information technology are encouraging schools to utilize digital media to enhance the quality of academic information services. SMPN 3 Sukaraja in Tasikmalaya Regency currently disseminates information via meetings, written notices, WhatsApp, and social media; consequently, information management is decentralized, difficult to track, and inefficient. This study aims to analyze requirements and design an academic website prototype to serve as a school information medium. The research employs the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), comprising stages for needs analysis, system design, prototype development, implementation, and evaluation. Data collection involved observation and interviews with school personnel to identify user needs and issues regarding information dissemination. The results indicate a need for a website-based information platform capable of centrally managing, storing, and disseminating information effectively, while ensuring easy access for teachers, students, parents, and the public. The designed academic website prototype features a school profile, announcements, news, teacher data, schedules, a gallery, and other academic information. Thus, the prototype is expected to improve the effectiveness of information dissemination, streamline data management, accelerate information access, and support the enhancement of information services within the school environment.